Various Immunization Routes, Times and Types to Prevent Newcastle Disease - ALHassan, Ali S. A.; Jasim, Nafea S. (American Journal of Biology and Natural Sciences, 2025)
We adopted different methods and types for administering the vaccine against Newcastle disease to 175 Ross 308 breed newly hatched chicks, one day age. First group G1 was vaccinated using eye instillation on the 1st day and then the same vaccine was repeated in the same way on 8th day and the vaccine was given to the second group(G2) in the same way but it was returned on 15th day of age .The third group (G3) was given the vaccine by spraying on 1st t day and revaccinated oil emulsion sub cutaneous on 5th days It was boosted with a second live vaccine by drinking method at 15th day age. The fourth group (G4) was vaccinated with drinking water on 10th day of the bird’s age and it was returned after ten days, leaving one group of them without vaccination, it was used as a control group (G5). Six group (G6) vaccinated with double vaccine (H9N2-ND) vaccine while group seven ( G7) immunized with ND rec .on MD at first day . ELISA test was performed to measure the size of the antibodies at different times of the bird’s age. The volumetric standard for antibodies resistant to the Newcastle disease virus of G3 increase significantly (p<0.0001) at value 5867 ±261.4 , 8980. ± 498.6 in 14th days and 24th day respectively . G1 that was given the vaccine by dropping in the eye on 1st day and repeated on 8th days increase significantly (p<0.0001) a value of 6898.2±347.1 compared with dropping in the eye 1st day and returned on 15th days (G2) of age 6758.7 ±232.8 at value .G4 that giving live vaccines using the drinking water method was gives results, but with a lower percentage of protection than the two mentioned methods with a value 5880.4±476.7 when measuring the volumetric antibodies standard on 24th day respectively of the bird’s age. Live vaccines in all ways increase significantly (P < 0.0001 ) volumetric antibodies titer means measured on 24th day than measured on 14th day and increase significantly (P < 0.0001 ) than control group (G5) which had a significant decrease (P<0.0001) means of the (705.2 ±505.01) on14th day to (313.1 ± 560.7 ) on 24th days. On other hand the recombinant vaccines for Newcastle disease (ND rec .on MD) vaccinated group increase significantly (P<0.0001) over two vaccinations dropping methods at different times, injection killed vaccine alone and two vaccinated drinking water method at different times with a value 7211.6 ± 550.2 . Double vaccine H9N2 –ND gave good results and did not affect the health of the birds, as a value of (6572±572.5) was recorded when measured on the 24th day of the birds’ age.